Human beta-defensin 2 is a salt-sensitive peptide antibiotic expressed in human lung. - Bals, R (1998)
Previous studies have implicated the novel peptide antibiotic human beta-defensin 1 (hBD-1) in the pathogenesis of cystic fibrosis. We describe in this report the isolation and characterization of the second member of this defensin family, human beta-defensin 2 (hBD-2). A cDNA for hBD-2 was identified by homology to hBD-1. hBD-2 is expressed diffusely throughout epithelia of many organs, including the lung, where it is found in the surface epithelia and serous cells of the submucosal glands. A specific antibody made of recombinant peptide detected hBD-2 in airway surface fluid of human lung. The fully processed peptide has broad antibacterial activity against many organisms, which is salt sensitive and synergistic with lysozyme and lactoferrin. These data suggest the existence of a family of beta-defensin molecules on mucosal surfaces that in the aggregate contributes to normal host defense.